Efeitos da reabertura de fronteiras terrestres em cidades-gêmeas na disseminação do SARS-CoV-2: estudo antes-depois controlado - Prada, Yury Lizeth Cardozo (2022)
Controlling the spread of SARS-CoV-2 has become a challenge for health authorities around the world, thus leading to the implementation of different strategies in each country to mitigate its spread. One of the hygienic actions implemented in the South American axis was the closing of international land borders, aiming to avoid the emigration flow between twin cities, as they are considered a geographically susceptible space for the international circulation of diseases. In this before-and-after controlled study based in Brazilian municipalities, we investigated the effects of reopening land borders in twin cities on the spread of infection and mortality from COVID-19 by comparing localities where the international border was reopened (intervention group) with those where the international border remained closed (control group). Furthermore, factors associated with the incidence of COVID-19 in Brazilian twin cities before and after the opening of international land borders were examined. We extracted all records of new cases and deaths that occurred in Brazilian twin cities between the months of August and December 2020. The MannWhitney U test was used to compare the groups evaluated and the Wilcoxon test was used to test the association between border opening and incidence and mortality rates. In parallel, a case-control study was conducted. Fisher's exact test was employed to check the factors associated with the increase in incidence rate after the opening of the land borders. No association was observed between border opening and the incidence rate of COVID-19 in the Brazilian twin cities, being (381.00 (261.31 - 932.96) vs 394.64 (163.23 -957.03) cases per 100. 000 population, z = 1.09, p = 0.27), nor in the intervention group (246.89 (222.17 - 549.26) vs 231.70 (179.15 - 646.25) cases per 100,000 population, z = 0.20, p = 0.84). The same occurred when analyzing mortality rate; there was no statistically significant change in either the control group (6.36 (2.09-14.66) vs 7.14 (2.88-16.79) deaths per 100,000 population, z = 0.53, p = 0.59), or the intervention group (6.86 (5.23- 16.54) vs 4.44 (2.86-11.88) deaths per 100,000 population, z = 1.53, p = 0.12). Population size (x2(2) = 0.88; p = 0.67), presence of airports in the twin cities (x2(1) = 0.45; p = 1.00), distance between the twin cities and neighboring foreign cities (x2(1) = 1.58; p = 0.21), and border type (x2(2) =1.12 p = 0.57) were found not to be associated with the incidence rate of COVID-19. We conclude that the reopening of international land borders in Brazilian twin cities did not change the behavior of incidence and mortality rates.